A novel alphaproteobacterial ectosymbiont promotes the growth of the hydrocarbon-rich green alga Botryococcus braunii - Tanabe, Yuuhiko (Sci Rep, 2015)
Botryococcus braunii is a colony-forming green alga that accumulates large amounts of liquid hydrocarbons within the colony. The utilization of B. braunii for biofuel production is however hindered by its low biomass productivity. Here we describe a novel bacterial ectosymbiont (BOTRYCO-2) that confers higher biomass productivity to B. braunii. 16S rDNA analysis indicated that the sequence of BOTRYCO-2 shows low similarity (<90%) to cultured bacterial species and located BOTRYCO-2 within a phylogenetic lineage consisting of uncultured alphaproteobacterial clones. Fluorescence in situ hybridization (FISH) studies and transmission electric microscopy indicated that BOTRYCO-2 is closely associated with B. braunii colonies. Interestingly, FISH analysis of a water bloom sample also found BOTRYCO-2 bacteria in close association with cyanobacterium Microcystis aeruginosa colonies, suggesting that BOTRYCO-2 relatives have high affinity to phytoplankton colonies. A PCR survey of algal bloom samples revealed that the BOTRYCO-2 lineage is commonly found in Microcystis associated blooms. Growth experiments indicated that B. braunii Ba10 can grow faster and has a higher biomass (1.8-fold) and hydrocarbon (1.5-fold) yield in the presence of BOTRYCO-2. Additionally, BOTRYCO-2 conferred a higher biomass yield to BOT-22, one of the fastest growing strains of B. braunii. We propose the species name ‘Candidatus Phycosocius bacilliformis’ for BOTRYCO-2.